Coregulation of glutamine synthetase1;2 (GLN1;2) and NADH-dependent glutamate synthase (GLT1) gene expression in Arabidopsis roots in response to ammonium supply - Kojima, Soichi; Minagawa, Haruka; Yoshida, Chika; Inoue, Eri; Takahashi, Hideki; Ishiyama, Keiki (Frontiers in Plant Science, 2023)
Ammonium absorbed by roots is assimilated into amino acids. The glutamine synthetase/glutamate synthase (glutamine 2-oxoglutarate aminotransferase) (GS/GOGAT) cycle is essential to this biological process. In Arabidopsis thaliana, GLN1;2 and GLT1 are the GS and GOGAT isoenzymes induced in response to ammonium supply and playing key roles in ammonium utilization. Although recent studies suggest gene regulatory networks involved in transcriptional regulation of ammonium-responsive genes, direct regulatory mechanisms for ammonium-induced expression of GS/GOGAT remain unclear. In this study, we revealed that the expression of GLN1;2 and GLT1 in Arabidopsis is not directly induced by ammonium but is regulated by glutamine or post-glutamine metabolites produced by ammonium assimilation. Previously, we identified a promoter region required for ammonium-responsive expression of GLN1;2. In this study, we further dissected the ammonium-responsive region of the GLN1;2 promoter and also performed a deletion analysis of the GLT1 promoter, which led to the identification of a conserved ammonium-responsive region. Yeast one-hybrid screening using the ammonium-responsive region of the GLN1;2 promoter as a decoy sequence revealed a trihelix family transcription factor DF1 that binds to this region. A putative DF1 binding site was also found in the ammonium-responsive region of the GLT1 promoter.